The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/en16010466
|View full text |Cite
|
Sign up to set email alerts
|

Households’ Energy Transformation in the Face of the Energy Crisis

Abstract: The purpose of conducted research was to recognize factors determining households’ Energy transition and barriers that slow that process. Energy transition itself, understood as a shift in the structure of fuels used in energy production and technological changes related to its use, are key elements of shaping the economy. It was determined to what extent existing household renewable energy installations meet the energy needs of their residents and what factors encourage their installation. In addition, barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…A study by O'Malley et al [29] also stated that limited access to finance is a key barrier to energy efficiency. More recent studies, such as those by Lou et al [30] and Jadwiga et al [31], again reinforce the financial factor as the most significant barrier for users.…”
Section: Barriers To Decisions On Energy Renovation In Buildingsmentioning
confidence: 77%
See 1 more Smart Citation
“…A study by O'Malley et al [29] also stated that limited access to finance is a key barrier to energy efficiency. More recent studies, such as those by Lou et al [30] and Jadwiga et al [31], again reinforce the financial factor as the most significant barrier for users.…”
Section: Barriers To Decisions On Energy Renovation In Buildingsmentioning
confidence: 77%
“…On the benefits of the energy improvement of buildings to the quality of life and the environment, Jadwiga et al [31] showed in their study that, despite some negative effects of the energy transition, they attach more importance to its beneficial aspects.…”
Section: Barriers To Decisions On Energy Renovation In Buildingsmentioning
confidence: 99%
“…In this context, the promotion of this direction of change is strongly emphasised in the literature, where sustainable development is captured as a critical direction in the evolution of the world's economies, and the role of households in this process is widely explored and highlighted [47,48]. The positive impact of RES in this area is emphasised, among others, by A. Biernat-Jarka et al, who conducted a similar study on practical choices of RES solutions, drawing attention to their role in reducing the level of energy poverty, which in Poland affects as much as 9% of the community [49], as energy expenses constitute one of the main burdens on household budgets [50] E. J. Szyma ńska et al in a similar strand of research point to similar choices in practical terms, articulating at the same time the barriers to the development of this dimension of household activity [44], which, as noted by D. Štreimikien ė et al are gradually being eliminated in the world [51]. M. Makešová et al, point to the impact of the RES dimension development on the process of strengthening economic well-being while emphasising the vital importance of this dimension in the process of energy systems transformation, giving grounds for locating it among the integral elements of this process [52].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the odds ratio change scale exp( βj ) of the logit model βj determine the OR values, where the average change is created by a unit increase in the variable [41,42]. The practice of this approach to the study of qualitative dichotomous variables is evident in the literature [43,44].…”
Section: Innovative Green Technology Solutions In Polish Households-a...mentioning
confidence: 99%
“…Guan et al (2023) described the worldwide increase [5], and Saligkaras and Papageorgiou (2022) outline the European increase in household electricity prices [6]. Szymańska et al (2023) found that Polish prosumers are less concerned about the energy crisis and its price increase than non-prosumers [7].…”
Section: A Impact Of Europe's Energy Crisis On Consumption Behaviormentioning
confidence: 99%